Authigenic 10Be/9Be ratio signature of the Matuyama-Brunhes boundary in the Montalbano Jonico marine succession - Simon, Quentin; Bourles, Didier; Bassinot, Franck; Nomade, Sébastien; Marino, Maria; Ciaranfi, Neri; Girone, Angela; Maiorano, Patrizia; Thouveny, Nicolas; Choy, Sandrine; Dewilde, Fabien; Scao, Vincent; et al. (Earth and Planetary Science Letters, 2017)
International audience Geomagnetic dipole moment (GDM) lows associated with polarity reversals or geomagnetic excursions induce significant modulation of the cosmogenic nuclide Beryllium-10 (10Be) production. Hence, the reconstruction of atmospheric 10Be production rates from natural archives such as marine sedimentary sequences or ice cores constitutes a complementary approach, independent from paleomagnetic measurements, to decipher past GDM fluctuations. This is particularly important in the Montalbano Jonico succession (South Italy) since it is candidate to host the Global Stratotype Section and Point of the Middle Pleistocene Stage but where the magnetostratigraphic positioning of the Matuyama–Brunhes boundary (MBB) has not been available up to now. This study presents (1) original authigenic 10Be cosmogenic nuclide and 9Be stable isotope results, and (2) new high-resolution benthic oxygen isotope record covering termination IX and Marine Isotope Stage (MIS) 19. A robust chronological framework is established on the basis of (i) our oxygen isotope stratigraphy, using the strong analogies between MIS 1 and MIS 19c in terms of orbital forcing and CO2level, and (ii) one precise 40Ar/39Ar date obtained in the tephra layer V4. The authigenic 10Be/9Be ratio record marks the atmospheric 10Be overproduction linked to the dipole low accompanying the MBB transition, with a characteristic twofold increase of the 10Be production at the end of MIS 19c and early MIS 19b. This signature is similar to those described in both marine and ice core records. The detailed chronostratigraphy constrained by a radiometrically-dated tephra layer (773.9 ±1.3ka) within the MBB interval, makesit possible to discuss the structure and to assess the timing of the 10Be-production changes, and thus the MBB geomagnetic variations, with an unprecedented accuracy for a marine archive (sedimentation rates ∼80cm/ka). These new cosmogenic nuclide production signatures provide the only missing constraint required for retaining the Montalbano ...